Evaluasi Pengendalian Internal dan Akuntabilitas Karyawan terhadap Keterlambatan Pengiriman Barang - Febrianti, Adhellia Zuriska; Auliyah, Robiatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to evaluate internal control and employee accountability for late delivery of goods in a Manufacturing Company located in East Java. This research uses a qualitative method with an analytical descriptive approach to get an in-depth picture of how employee accountability affects delays in goods delivery. The results showed that employee accountability for late delivery of goods was still low. Several factors, including incorrect input of stock materials, item leaks, jobdesk adjustments, lack of coordination or confirmation, employee negligence, lack of attention to targets, and jobdesk errors, cause this. Previous research wanted to assess the impact of the internal control system on the effectiveness of the banking industry. Meanwhile, this study was conducted in the context of manufacturing companies and added employee accountability variables.